Forced Oscillation of a Certain System of Fractional Partial Differential Equations - Ramesh, R.; Prakash, P.; Harikrishnan, S. (Journal of Applied Nonlinear Dynamics, 2026)
In this paper, we consider a system of fractional partial differential equations subject to Dirichlet and Neumann boundary conditions. Several sufficient conditions are established for forced oscillation of solutions of such systems. Examples are given to illustrate our main results.